ABCC11/MRP8 polymorphisms affect 5-fluorouracil-induced severe toxicity and hepatic expression. (September 2013) - Magdy, Tarek; Arlanov, Rudolf; Winter, Stefan; Lang, Thomas; Klein, Kathrin; Toyoda, Yu; Ishikawa, Toshihisa; Schwab, Matthias; Zanger, Ulrich M
Aim: Because 5-fluorodeoxyuridine monophosphate (5-FdUMP), an anabolic active metabolite of 5-fluorouracil (5-FU), is a substrate of MRP8 (encoded by ABCC11 ), we investigated whether ABCC11 polymorphisms play a role in severe toxicity of 5-FU.Patients & methods: Genomic DNA from 672 cancer patients treated with 5-FU monotherapy and with documented toxicity according to WHO criteria was genotyped for 12 ABCC11 tag SNPs. Functional impact of polymorphisms was assessed in a Caucasian human liver cohort (n = 150) and by recombinant expression of MRP8 protein variants.Results: Univariate and multivariate analysis identified rs17822471 (G>A, T546M) as risk factor of severe leukopenia (p = 0.021, odds ratio [95%CI]: 3.31 [1.26–8.66]) but not of other toxicity types. MRP8 protein expression in human liver was 1.7-fold lower in carriers compared with wild-type (p = 0.02). Recombinant expression confirmed the effect of T546M on protein expression.Conclusion: Since MRP8 is expressed in bone marrow blasts and leukocytes, lower expression may lead to intracellular accumulation of 5-FdUMP and increased risk of leukopenia. Original submitted 25 April 2013; Revision submitted 17 July 2013